Risk Risk Mitigation on Asphalt Mixing Plant Process in Bali - Wardani, A.A.A Made Cahaya (International Journal of Engineering and Emerging Technology, 2020)
Risk Mitigation on Asphalt Mixing Plant Process in Bali AAA Made Cahaya Wardani 1 , I Nyoman Arya Thanaya 2 , I Nyoman Yudha Astana 3 , AA Gde Agung Yana 4 Student of Doctoral Program Engineering Science Udayana University,Denpasar,Bali, Indonesia 2,3,4 Lecture of Doctoral Program Engineering Science Udayana University, Denpasar, Bali,Indonesia Email : agungcahaya@unhi.ac.id   ABSTRACT   The need for asphalt to meet the handling of the National road project which has been fulfilled by Pertamina as a partner providing asphalt is believed to be able to meet the needs of up to 45 to 50 percent (1.2 million to 1.4 million tons per year). In Bali Province, with a length of 629.39 km of National Roads and 743.34 km of Provincial Roads (PUPR Office of Bali Province, 2018). For Fiscal Year 2018, the need for Asphalt in Routine Rehabilitation / Maintenance Activities for Roads and Bridges is 25,842 tons of asphalt (PUPR Bali Prov. 2018) and the quantity requirement for asphalt for Road and Bridge Improvement Work Packages in Fiscal Year 2018 is 195,657.6 tons. So that the risk of asphalt procurement by its suppliers requires effective handling.This study focuses on mitigating major risks that occur in the road works supply chain, namely identifying risk mitigation in the production and operational processes of the Asphalt Mixing Plant (AMP) production unit related to road infrastructure construction work in Bali Province.                 The first study focuses on mitigating major risks that occur in the road works supply chain, namely identifying risk mitigation in the production and operational processes of the Asphalt Mixing Plant (AMP) production unit related to road infrastructure construction work in Bali Province has been completed. This study focus on the second stage of risk mitigation that is data collection regarding ISM mitigation and assessment through Focus Group Discussions which will be held after the first stage is completed, the selection of FGD members is carried out by people who have expertise and competence in their fields consisting of: Contractors, Consultants, project owners, academics and competent people in AMP management. From the study found 80 points of mitigation from major risk based on SIPOC stage of asphalt production. This risk mitigation is elaborated into Total Quality Management, and  catagorized into 11 catagory of risk mitigation elements of Risk Mitigation Model based on Total Quality Management.   Keywords : Risk Mitigation, Interpretive Structural Model, Focus Group Discussion